Fuzzy proportional-integral controlled unified power quality conditioner for electric vehicle charging grids - S, Sumana; H, Tanuja; J, Supriya; Gunaga, Shruti R (Institute of Advanced Engineering and Science, 2025)
In power system one of the major concerns is the power quality (PQ) issues due to the presence of non-linear loads. At present electric vehicles (EV’s) are highly desired for mobility but it has challenges related to power quality. EVs are primarily charged either from the grid or renewable sources like photovoltaic (PV) cells, which function as direct current (DC) grids. However, the growing number of EV’s can introduce disturbances in voltage and harmonics in current. This has necessitated a user-friendly method to rectify these imbalances. The uniqueness of this work is that, the investigations are carried out to prove the effectiveness of the PV powered unified power quality conditioner (UPQC) in resolving the disturbance created by EV charger and dynamic load both in grid connected as well as in off grid mode of operation in standard IEEE 14-bus microgrid model distribution system. The approach of intelligent fuzzy-proportional-integral (fuzzy-PI) controller in regulating the performance of the PV powered UPQC is another novel approach. Case studies based on the performance of UPQC is done for various scenarios of EV charger and its performance is compared with conventional PI controller. Simulations are carried out in MATLAB2017b software package.